Consumer behavior in shopping day promotion: case from Indonesian gen z - Wicaksono, Adhika Putra (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
The transition from traditional to digital business is one of the main factors a business requires to survive in the technological era. Indonesians have shopping behavior concerns about shopping day promotion offered by e-commerce. Due to the large number of transactions during the shopping day promotion, the seller risk of late goods shipment late is getting higher. It is caused by massive transactions processed by the seller.  This study wants to know what factors influence customer satisfaction with the shopping experience on shopping day promotions. Furthermore, this research wants to discover whether customer shopping satisfaction can influence the desire to repurchase on shopping day promotions and spread it to other people. This study analyzed 251 questionnaires and processed them using structural equation modeling (SEM). The results of this study state that overall e-service quality is influenced by three dimensions, namely website design, customer service, and fulfillment; customer satisfaction is affected by all e-service quality, savings, and product quality; and customer satisfaction influences repurchase intention and word of mouth (WOM). This research suggests retailers who sell on e-commerce and e-commerce itself take advantage of SDP in order to be able to compete in an increasingly tight business environment